Selection of Agar Reagents for Medium Solidification Is a Critical Factor for Metal(loid) Sensitivity and Ionomic Profiles of Arabidopsis thaliana - Uraguchi, Shimpei; Ohshiro, Yuka; Otsuka, Yuto; Tsukioka, Hikari; Yoneyama, Nene; Sato, Haruka; Hirakawa, Momoko; Nakamura, Ryosuke; Takanezawa, Yasukazu; Kiyono, Masako (Frontiers in Plant Science, 2020)
For researchers in the plant metal field, the agar reagent used for the solid plate medium is a problematic factor because application of different agar types and even a different lot of the same agar type can mask the plant metal-related phenotypes and impair the reproducibility. In this study, we systematically assessed effects of different agar reagents on metal(loid) sensitivity and element accumulation of the Arabidopsis metal sensitive mutants. Three established mutants (cad1-3, cad1-6, and abcc1/2), and three different types of purified agar reagents (Type A, Type E, and Nacalai) with two independent batches for each reagent were subjected to the analyses. First, we found that element concentrations in the agar reagents largely varied among the agar types. Then the effects of agar reagents on the mutant metal(loid)-sensitivity were examined under As(III), Hg(II), Cd(II), and excess Zn(II) conditions. A significant variation of the mutant metal(loid)-sensitivity was observed among the different agar plates but the variation depended on the combination of metal(loid) stress and agar reagents. Briefly the type-dependent variation was more evident under As(III) and Hg(II) than Cd(II) or excess Zn(II) conditions. A lot-dependent variation was also observed for Type A and Type E but not for Nacalai: hypersensitive phenotypes of cad1-3, cad1-6, and abcc1/2 under As(III) or Hg(II) treatments were diminished when different batches of the Type A or Type E agar types were used. We also found a significant variation of As and Hg accumulation in the wild-type and cad1-3. Plant As and Hg concentrations were remarkably higher and the difference between the genotypes was more evident when grown with Type A agar plates. We finally analyzed ionomic profiles in the plants exposed to As(III) stress. Agar-type specific ionomic changes in cad1-3 were more observed with the Type A plates than with the Nacalai plates. The presented results overall suggest that suitability of agar reagents for metal(loid)-related phenotyping depends on the experimental design, and an inappropriate selection of agar reagents can mask even very clear phenotypes of the established mutant like cad1-3. We also discussed perspectives on the agar problem in the plant metal study.